Peran Tata Kelola Perusahaan, Kinerja Auditor, Ukuran KAP terhadap Kualitas Audit pada Sektor Keuangan yang Terdaftar di BEI - Siti Aisyah; Nungki Kartikasari (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
This study investigates how corporate governance, auditor performance, and public accounting firm size affect audit quality in financial sector companies listed on the Indonesia Stocck Exchange (IDX) during the audit period of 2020-2023. This study took a purposive sample, resulting in 324 company samples. The data were tested using multiple linear regression. Governance has a negative effect on audit quality, while auditor performance does not affect audit quality, KAP size almost affects audit quality in a negative direction. Keywords: Corporate Governance; Audit Performance; Audit Firm Size; Audit Quality